Radar Tasikmalaya News Portal's Error Analysis in the Indonesian Language from a Linguistic Category Point of View - Nurjamilah, Ai Siti; Nores K., Welly; Rosiana, Shinta; Wijayanti, Sri Hapsari; Solissa, Everhard Markiano; Saputra, Nanda (LPPM Undiksha, 2023)
There are still many online news portals that make writing errors, not only in terms of spelling, but also in terms of morphology, syntax and semantics. The goal of this language mistake analysis is to analyze and repair phonological, morphological, syntactic, and semantic faults found on instructional pages of the Radar Tasikmalaya news site. The researcher employed a descriptive analytic method. The research methods employed in this study were observation, interviews, and literature studies, which involved reviewing all of the books, articles, notes, and reports that had anything to do with the issue being addressed. By performing numerous steps in the study process, including: (1) gathering data, (2) describing the data, (3) evaluating the data, and (4) drawing conclusions. The findings of a language mistake study for the Radar Tasikmalaya news portal's edition can be concluded that there are forms of language errors in the fields of phonology, morphology, syntax, and semantics. In linguistic-morphological category errors there are errors in affixation. Syntactic errors consist of errors in sentence construction. There are also semantic errors consisting of errors in the meaning of sentences that can make the reader misinterpret the sentence. Then there are errors in the use of spelling or phonology, these spelling errors consist of writing errors in the use of punctuation marks, especially in writing academic degrees, using standard words, writing foreign terms, and writing capital letters.